ANALISIS NILAI PENDIDIKAN DALAM CERPEN “SI KUCING YANG SANGAT ANJING” KARYA SASTI GOTAMA DAN “ANAK TUNGGAL SEORANG DUKUN” KARYA ILHAM SAFUTRA - Kirmawati, Kirmawati (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
This study aims to examine the educational values embedded in two short stories published in Jawa Post April 2025, namely “Si Kucing yang Sangat Anjing” by Sasti Gotama and “Anak Tunggal Seorang Dukun” by Ilham Safutra. The research employed a descriptive qualitative method using content analysis. The data consist of textual excerpts reflecting religious, moral, social, and cultural values. The findings reveal that both stories present moral values such as responsibility, honesty, courage in decision-making, and self-control. Religious values are represented through expressions of faith and spiritual awareness in interpreting life experiences. Social values emerge from depictions of solidarity, critique of societal stigma, interpersonal relationships, and the influence of social media. Cultural values involve local beliefs, traditional practices, and social stratification within the community. Thus, the stories function not merely as literary entertainment but also as a medium for character education, offering meaningful insights for readers